Benchmark approach to search of cost‐effective and accurate density functional for homolytic cleavage of C─Mg bond of Grignard reagent. Issue 4 (14th November 2019) - Kosar, Naveen; Ayub, Khurshid; Gilani, Mazhar A.; Shah, Faheem; Mahmood, Tariq
Abstract: Grignard reactions are of importance in organic chemistry for the synthesis β ‐keto esters and diethyl malonate, alcohols, aldehydes or ketones, monocarboxylic acids, and other organometallic compounds. Generally, the heterolytic dissociation of C─Mg bond in Grignard reagent is the key step in these reactions. Recently, homolytic cleavage of the C─Mg bond in Grignard reagents has been reported in the preparation of stable radicals. These reactive species react with other compounds, which result in the formation of hydrocarbons and their derivatives. Therefore, the study of homolytic cleavage of C─Mg bonds is quite vital to better understand the kinetics and thermodynamics of these reactions. In the current study, a benchmark approach is adopted to find a cost‐effective and accurate density functional (DF) for bond dissociation energies measurement of the C─Mg bond of Grignard reagents. Twenty‐nine DFs from 13 density functional theory (DFT) classes with three types of basis sets (Pople' 6‐31G(d) and 6‐311G(d), Dunning's aug‐cc‐pVDZ, and Karlsruhe' def2‐SVP basis sets) are implemented for the measurement of dissociation energies of the C─Mg bond. Theoretical dissociation energy values are compared with experimental reported values of the C─Mg bond of selected Grignard reagents. TPSSTPSS of the meta‐GGA class with 6‐31G (d) basis set gave accurate results, and its Pearson's correlation is 0.95. SD, root mean square deviation, and mean unsigned error of this method are 2.36 kcal mol −1, 2.33 kcal mol −1, and −0.46 kcal mol −1, respectively. TPSSTPSS of the meta‐GGA class is a one‐electron, self‐interaction, error‐free Tao‐Perdew‐Staroverov‐Scuseria functional that performed better with the 6‐31G(d) basis set. Abstract : A benchmark approach is adopted to search for a cost‐effective and accurate density functional for the homolytic cleavage of the C─Mg bond of Grignard reagents. Out of 29 density functionals in combination with four different basis sets, TPSSTPSS/6‐31G (d) best describes the C─Mg bond dissociation energies.